MUATAN KEILMUAN INTEGRASI INTERKONEKSI PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI (Telaah Kurikulum 2013 Jenjang SMA) - Wiji Hidayati (Jurnal Pendidikan Agama Islam, 2015)
This research is a library research aimed at describing the scientific content of the integration interconnection aspect of the Islamic Education and Character Education of the 2013 Curriculum at Senior High Schools. Documentation method is conducted to collect data. Content analysis is used as data analysis technique based on Al-Jabiri’s epistemology namely, bayani, irfani, and burhani, while the integration-interconnection aspect of science is based on M.Amin Abdullah’s hypothesis with circular model incorporating Al-Jabiri’s three scientific epistemology. Hence, it is concluded that the aspect of the integration-interconnection of the Islamic Education and the Character Education of the 2013 Curriculum at Senior High School stated in the Regulation of the Ministry of Education and Culture No.69 year 2013 fulfilled the circular model of bayani, irfani and burhani is apparent in 4 chapters (13%), while there are 22 chapters (71%) which accomplished two aspect of Al-Jabiri’s scientific epistemology, and 5 chapters (16%) rooted only in bayani.